Protecting police officers against burnout: Overcoming a fragmented research field - Correia, I.; Romão, Â.; Almeida, A. E.; Ramos, S. (Journal of Police and Criminal Psychology, 2023)
This study aims to identify the determinants of burnout in police officers. We considered a wide range of psychosocial risk factors, individual variables that have been previously found to be associated with burnout in police officers (affective and cognitive empathy, self-care), and variables whose unique impact on burnout of police officers needs further clarification (organizational justice and organizational identification). The study was conducted in Portugal, and the sample was constituted by 573 members of the National Republican Guard (GNR—Guarda Nacional Republicana). The participants were invited to answer an online anonymous survey, which included previously validated measures of the following variables: burnout (exhaustion and disengagement), psychosocial risk factors, self-care, empathy (cognitive and affective), organizational justice, and organizational identification. Furthermore, we controlled for the potential impact of demographic variables (age, gender, years of professional experience, religiosity, political orientation, and income). Multiple regression analysis showed that when taken together, only a few of the variables associated with burnout had a unique impact on both exhaustion and disengagement: quantitative demands and affective empathy were burnout risk factors; meaningful work, organizational justice (distributive justice, procedural justice, and interactional justice), and organizational identification were burnout protective factors. Our results highlight the importance of developing theoretical models and planning interventions to prevent burnout in police officers, focusing mainly on the above-mentioned variables.